Pendidikan Kewirausahaan Dalam Prespektif Idealisme Santripreneur - Ahmad Saifudin (Intizam, Jurnal Manajemen Pendidikan Islam, 2019)
Our country is a country that has countless natural resources. All the potential both in the economic field and large natural resources, with the potential for abundant natural wealth, with a large enough population is needed Reliable resources and have a clear literary, meaning that the skills in designing each component will be able to meet the needs of quality labor. Educational institutions as a place to form a generation that is aware, and has the responsibility in producing reliable human resources, both physically and spiritually, for example the existence of Islamic boarding schools in Indonesia is an educational institution that has a distinctive character in the formation of human character and has been able to save the nation This is from destruction, through the Santripreneur program it is expected to be able to change the santri polafikir which has been underdeveloped in the economic sector, business development in the small and medium industry sector (IKM) in the pesantren environment. Based on data from the Ministry of Religion, in 2014, with an estimated number of pesantren there were 27,290 institutions, with a total number of 3.65 million santri students. Santripreneur program is an embodiment of the Map of the journey of the Indonesian people towards era 4.0, in the rank of empowerment in the Small and Medium Industry sector